The effect of sugarcane fiber volume fraction and variations in NaOH immersion on polyester matrix with impact strength - Haryoszi, Haryoszi; Juanda, Juanda; Erwansyah, Erwansyah (JTTM : Jurnal Terapan Teknik Mesin, 2026)
The development of material technology demands the availability of materials that have high mechanical strength but remain lightweight and environmentally friendly. One potential alternative is a natural fiber-based composite material. Bagasse fiber, as a waste product of the sugar and beverage industry, has a high cellulose content so it has the potential to be used as a reinforcement material in composites. However, the surface character of the fiber, which still contains lignin and hemicellulose, needs to be modified so that it can bond well with the polyester matrix. This study aims to analyze the effect of variations in the volume fraction of bagasse fiber and the duration of immersion in NaOH solution on the impact strength of polyester-based composites. Sugarcane fiber was immersed in a 5% NaOH solution with varying times of 60, 90, and 120 minutes, and combined with three fiber volume fractions, namely 13%, 15%, and 17%. Specimens were prepared using the hand lay-up method and impact testing was carried out according to the ISO 179-1 standard using the Charpy impact test method. The test results showed that the combination of fiber fraction and immersion time had a significant effect on the toughness of the composite. The highest impact strength value of 51.5 kJ/m² was obtained at a fiber volume fraction of 13% with a soaking time of 120 minutes, while the lowest value of 25.6 kJ/m² was obtained at a fraction of 17% with the same soaking duration. In general, a soaking time of 90 minutes produces the best impact strength stability because it produces a balance between the cleanliness of the fiber surface and the integrity of its cellulose structure. Based on these results, bagasse fiber composites have proven to have great potential as an environmentally friendly alternative material that can be applied to automotive components such as car dashboards, replacing conventional synthetic materials.